SQ3R Method as A Solution To Improve Reading Comprehension Skills in Elementary School - Rini Endah Sugiharti; Ratna Duhita Pramintari; Intan Destianingsih (Universitas Pendidikan Indonesia (UPI), 2020)
The Scientific Work (KTI) is entitled